Regarding the projects for the promotion of peasant women - Galer, Nora (1985)
A significant number of projects specifically oriented to the promotion of rural women are currently being developed throughout the country. Parallel to the programs implemented by the public sector (CIPA, Ministry of Labor and Social Promotion), non-governmental organizations have designed localized coverage actions aimed at serving this sector of the population. Various events in recent years have brought together the promoters involved in these actions and through discussions and workshops a common problem has begun to be configured for this type of action. Our intention here is to evoke some of the converging problems detected and outline some guidelines that allow us to fine-tune the approaches of the projects and optimize the impact of the actions.